Analysis of Test Items for the 10th-Grade Visual Arts Course Using ANATES Software Version 4.0.9 - Miftahul Jannah; Rufi’I; Sabariah (PT Publikasiku Academic Solution, 2026)
Learning evaluation is an important component of the educational process for obtaining information regarding the achievement of learning objectives and students’ abilities. The accuracy of evaluation results is greatly influenced by the quality of the instruments used; therefore, test item analysis is necessary as a basis for determining the characteristics and feasibility of each test item. This study aimed to analyze the quality of Class X Visual Arts subject test items on the material Introduction to Fine Arts Around Us using ANATES software version 4.0.9. The study employed a quantitative descriptive approach involving 36 students. The analyzed instrument consisted of 25 multiple-choice questions. The analysis included test reliability, difficulty level, discriminating power, and distractor quality. The test result data were analyzed using ANATES software version 4.0.9 and interpreted based on the criteria for each test item analysis indicator. The results showed that the instrument had a reliability coefficient of 0.49, which was categorized as moderate. The difficulty level analysis revealed that the items were dominated by very easy and easy categories, while the discriminating power varied from very poor to very good. Most distractors functioned effectively, although several items still required improvement. In conclusion, the test instrument was considered reasonably feasible for use as a learning evaluation tool; however, revisions are still needed for several items. The analysis results can serve as a basis for teachers to improve and develop higher-quality evaluation instruments capable of measuring students’ abilities more accurately.